Development and characterization of EST-cSNP markers in Miichthys miiuy - XU Tian-jun; SUN Yue-na; SHI Ge; WANG Ri-xin (浙江大学学报. 农业与生命科学版)
To promote molecular-assisted breeding in Miichthys miiuy, a normalized full-length cDNA library was established to develop the EST-cSNP markers using the double-specific nuclease normalization method combined with switching mechanism at 5 end of RNA transcript technique. The results showed that a total of 5 053 expressed sequence tags (EST) were obtained, 4 609 high quality EST sequences in which were generated. For mining single nucleotide polymorphism (SNP) from EST sequences, 707 contig sequences were assembled by Vector NTI 11.0 software. A total of 209 putative and reliable SNPs were detected in all contigs. The appearance frequency of SNPs was 0.743 SNP per 100 bp in the obtained SNP sequences. Among these SNPs, 114 of which were transition, 74 were transversion and the other 21 were indels. The overall ratio of transition to transversion was 1.54. Gene annotation indicated that some SNP-containing genes belonged to immune-related genes that encoded major histocompatibility complex, immunoglobulin, T-cell receptor and other protease, respectively, showing that the identified SNPs were useful for studying molecular genetics and molecular-assisted breeding in M. miiuy.